Hunting to Feel Human, the Process of Women's Help-Seeking for Suicidality After Intimate Partner Violence: A Feminist Grounded Theory and Photovoice Study - Petrea Taylor (SAGE Publishing, 2020)
Women reach out to health care providers for a multitude of health problems in the aftermath of intimate partner violence, including suicidality; however, little is known about how they seek help. The purpose of this study was to explore how women seek help for suicidality after intimate partner violence using a feminist grounded theory and photovoice multiple qualitative research design. Interviews were conducted with 32 women from New Brunswick, Canada, and seven from this sample also participated in five photovoice meetings where they critically reflected on self-generated photos of their help-seeking experiences. Data were analyzed using the constant comparative analysis of grounded theory. Hunting to Feel Human involves fighting for a sense of belonging and personal value by perceiving validation from health care providers. Women battled System Entrapment , a feeling of being dehumanized, by Gauging for Validation and Taking the Path of Least Entrapment. Implications for health care providers include prioritizing validating interactions and adopting a relational approach to practice.